THE IMPACT OF MOVING TO KNOWLEDGE BASED ECONOMY IN THE PUBLIC SECTOR - Mihaela PACESILA (Management & Marketing)
Global economy underwent profound changes in the last fifteen years, whichdetermined the appearance of a new economy – the knowledge economy.This economy is the result of the knowledge revolution, which gets a greaterand greater importance. Knowledge development is also very important inpublic sector. The knowledge society and its impact in public sectordevelopment is a critical area of study. The knowledge economy in publicsector requires the utilization of the knowledge in order to improve thetransparence, the services delivering to the citizens, for a bettercommunication with the citizens/users/clients and in order to improve theknowing degree of their needs. The transition to the knowledge economy inpublic sector has to take place in a decentralized, non-bureaucratic, cataliticand permissive environment, orientated to the results. In the same time, thepublic organizations must become knowledge based organizations, that havethe responsability and the flexibility to achieve the objectives publicly defined.In order to promote efficiently the development in the knowledge economy,the government must facilitate, instead of breaking, the process of economicchanges and modernizations, according as this modifications create newopportuneness and raised revenues. This must become as fast, selectiveand flexible as the economy and the society with which is mostly in contactand it must adopt the political decisions that serve the best the publicinterest.